Equipment and Technology for Subsurface Irrigation of Intensive Gardens in the Bukhara Region of the Republic of Uzbekistan - F. U. Zhuraev; G. Kh. Karimov (Сельскохозяйственные машины и технологии)
Experience shows that for the irrigation of intensive gardens, various types of equipment and technologies are used, such as continuous irrigation (invasive), drip irrigation, subsurface irrigation and other methods. All irrigation options have some shortcomings, such as water evaporation, high water consumption, high consumption of mineral fertilizers and energy. (Research purpose) To develop an automated system for subsurface irrigation of intensive gardens with groundwater using electric pumps and solar panels, and to create a mathematical model of soil moisture distribution. (Materials and methods) Special devices shaped as pegs were designed to supply water with dissolved mineral fertilizers directly into the root system of intensive gardens. The authors investigated the pegs’ geometric parameters and the criteria for their placement in the soil, taking into account the consumption of water and nutrients. The authors examined soil mechanical composition and salinity as well as its physical and mechanical, technological properties. (Results and discussion) It was found out that the installation of the peg facilitates soil moisturizing through the central pipeline within the radius of 1.55-1.75 meters at the depth of 0.7-0.9 meters. Three-four pegs, being equidistant from each other and inclined in relation to the vertical axis by 20-30 degrees, were placed around a tree. Water consumption was determined for various irrigation methods: for furrow irrigation (control) – 1125.7 cubic meters per hectare, for continuous irrigation (invasive) – 1812.3 cubic meters per hectare, for drip irrigation – 618.6 and subsurface irrigation – 506.4 cubic meters per hectare. (Conclusions) Based on the results of the experimental study carried out in farms with intensive gardens using various irrigation methods, continuous irrigation (invasive), drip irrigation and subsurface irrigation were compared in terms of water consumption. The results show that drip irrigation and subsurface irrigation ensure less water consumption than flood irrigation, by 46 per cent and 57 per cent respectively. It was found out that subsurface irrigation ensures 57 per cent water and 25-35 per cent mineral fertilizer economy, in comparison with the other methods of providing trees with water and nutrients.